Integrating Ubiquitous Language Learning into the Workplace: A Lifelong Learning Model for Corporate Employees in Multinational Companies - Fernando Castillo; Ethan Tan; Ava Lee (International Journal of Language and Ubiquitous Learning, 2025)
Background. Globalization and rapid digital transformation have increased the demand for continuous language learning among employees working in multinational corporations. Ubiquitous Language Learning (ULL), supported by mobile and cloud-based technologies, offers flexible, context-responsive opportunities for enhancing communicative competence beyond traditional training settings. Purpose. This study aims to design and evaluate a workplace-oriented ULL model that supports sustained English language learning among employees in multinational companies.   Method. A mixed-methods approach was employed, combining a quasi-experimental design involving 142 employees from three global corporations with qualitative insights from interviews and usage analytics. Results. Results showed significant improvements in employees' communicative performance, including enhanced vocabulary retention, greater confidence in cross-cultural interactions, and increased frequency of spontaneous workplace language use. Usage analytics demonstrated that learning effectiveness was highest when activities were integrated into authentic professional tasks rather than delivered as standalone modules. Conclusion. The study concludes that a well-designed ULL model promotes continuous, self-directed learning and supports employees' professional growth in multicultural corporate environments.